Effectiveness of the “IVAA-SCHILLER” program in secondary prevention of cervical cancer in obstetric students, Roosevelt University Huancayo-2021 - Suárez Reynoso , Liz Miriam (2022)
Objective: To determine the influence of the “IVAA-SCHILLER” program in secondary prevention of cervical cancer en students of the VII and VIII semester of the Professional School of Obstetrics of the Private University of Huancayo Franklin Roosevelt-2021. Material and methods: the scientific method was considered, of an applied type, with a pre-experimental design with pre and post test, the population consisted of 80 students from the VII and VIII semester; the sample was of 57 students determined by convenience, As a technique the survey and as an instrument the questionnaire. Results: of the entrance test, it was observed that 8.8% of the students achieved a score of 6, 1.8% achieved scores of 7 and 15, in addition to the 12.3% achieved a score of 8, 15.8% achieved score of 13 and 14 respectively; Regarding the  exit test, 17.5% achieved scores of 10,1 and 15, 36.8% obtained a score of2, 10.5% achieved a score of 14. Conclusions: there is a statistically significant difference in averages I the population between the entry trial and exit trial; Thus; the alternative Hypothesis (Ha) is accepted.